The enemy release hypothesis and Callosciurus erythraeus in Argentina: combining community and biogeographical parasitological studies - Gozzi, Ana Cecilia (2020)
The enemy release hypothesis (ERH) postulates that during the invasion process an introduced species is released from the natural enemies that regulate its populations, promoting its invasion success in the new environment. Callosciurus erythraeus is a sciurid native to Southeast Asia that has been successfully introduced into Argentina and other Asian and European countries. The aim of this study was to provide new parasitological data on this species and to compare it with studies in native and other introduced ranges under the framework of the ERH. We proposed two working hypotheses: (1) an analysis at the community level to compare the prevalence, abundance and identity of parasites of C. erythraeus and sympatric native mammals in the main invasion focus of Argentina, and (2) an analysis at the biogeographical level to compare parasite richness in native and introduced ranges of C. erythraeus and parasite prevalence and richness among introduced regions with different invasion success (using population density and spread as proxy variables). The community analyses indicated that C. erythraeus has lost its specific parasites in Argentina and that it has a lower level of parasitism than other native mammals. The biogreographical analyses indicated a lower macroparasite richness of C. erythraeus in introduced ranges compared to its native range. However, parasite richness in introduced ranges was not associated with population density and spread. The negative correlation between parasite prevalence and population parameters was mainly due to the low parasite prevalence of C. erythraeus in Argentina where this species shows high density and spread. The release of parasites of C. erythraeus in comparison to its native and other introduced ranges, the low acquisition of generalist parasites and the high population density and spread reached in Argentina are mostly in agreement with the expected outcomes based on the ERH. Further studies are needed to better understand the role of the ERH in the invasion success of this species.